496. Higher SARS-CoV-2 RT-PCR Cycle Threshold (Ct) Values Associated with Longer Symptom Duration Among Patients Hospitalized with COVID-19. (31st December 2020) - Brown, Lillian B; Winston, Lisa Gail; Haller, Barbara; Pham, Phong; Marcelo, Beatrice; Cheung, Wendy; Lynch, Kara; Jain, Vivek
Abstract: Background: Most diagnostic tests for SARS-CoV-2, the causative agent of COVID-19, are RT-PCR based. This method is sensitive but cannot distinguish replicating from non-replicating virus. RT-PCR cycle threshold (Ct) values are inversely correlated with viral load, and higher Ct values have been correlated with lower in vitro viral infectivity. However, relatively few data exist on the association between Ct values and patients' duration of symptoms remains unclear. We thus evaluated Ct values and symptom duration in a cohort of patients hospitalized with COVID-19. Methods: We assessed all patients admitted to San Francisco General Hospital between April 1 and May 18, 2020 with confirmed COVID-19 infection based on RT-PCR testing (Abbott m2000 platform). We included patients having diagnostic testing for suspected COVID-19 and patients having asymptomatic testing per hospital policy. For symptomatic patients, date of symptom onset was abstracted from hospital records, and time from symptom onset to test date was calculated. RT-PCR Ct values were manually extracted. Median Ct and IQR were calculated for patients with < 10 days of symptoms, ≥10 days of symptoms, and asymptomatic disease. Between-group comparisons were performed using the Kruskal-Wallis test. Results: Among 61 patients with positive RT-PCR tests, 40 patients reported < 10 days of symptoms at the time of testing, 15 reported ≥10 days of symptoms, and 6 were asymptomatic. The median Ct value was 14.2 cycles (IQR, 10.2, 18.3) among patients reporting < 10 days of symptoms, 19.7 cycles (IQR, 15.3, 23.9) among patients reporting ≥10 days of symptoms, and 26.3 (IQR, 25.0, 29.1) among asymptomatic patients. Ct values were significantly lower among patients with < 10 days of symptoms compared to patients with >=10 days of symptoms (p=0.01) and when compared to asymptomatic patients (p=0.0002) [Figure]. Cycle threshold (Ct) by days of symptoms at time of testing Conclusion: SARS-CoV-2 RT-PCR cycle threshold values were higher (indicating lower viral load) in patients with longer symptom duration and were highest in asymptomatic patients. These results add to emerging data suggesting that strategies for optimal isolation of patients in both community and hospital settings could be informed by a combination of symptom duration and RT-PCR Ct values. Disclosures: All Authors : No reported disclosures